FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN TAMU DALAM PEMILIHAN HOTEL SYARIAH PADA HOTEL NATAMA SYARIAH - Reza Syahputra Ginting; Alfi Amalia (CERED Indonesia Institute, 2023)
This study uses a quantitative approach. The population is 2,123 customers or guests of the 2021 Natama Syariah hotel and the sample used is 95 respondents, namely customers or guests of the Padangsidempuan Natama Syariah hotel. The data source used in this study is primary data obtained by distributing questionnaires to respondents. Data analysis techniques in this study were data quality tests, classic assumption tests, multiple linear regression analysis and hypothesis testing which was carried out using SPSS version 25 software. The results of location research and the application of Islamic ethics influenced the choice of sharia hotels at Hotel Natama Syariah Padang Sidempuan . With good service quality, easy-to-reach and strategic location with city facilities, customers will increase at the hotel. Facilities and prices do not affect the selection of sharia hotels at Hotel Natama Syariah Padang Sidempuan. So that the price strategy in competition does not affect the selection of sharia hotels and good facilities do not necessarily attract interest in choosing these sharia hotels. The factors in choosing a sharia hotel (quality of service, facilities, location, price and application of Islamic ethics) have a joint effect on the choice of Hotel Natama Syariah Padang Sidempuan.